Treatment-related Hypertension as a Prognostic Factor for De Novo Metastatic Hormone-sensitive Prostate Cancer: A Retrospective Real-world Evidence Study - Giuseppe Salfi; Martino Pedrani; Selin Candan; Vasile Urechie; Sara Merler; Lorenzo Ruinelli; Amos Colombo; Luis Castelo-Branco; Irene Testi; Fabio Turco; Luigi Tortola; Ursula Vogl; et al. (European Urology Open Science)
Background and objective: Hypertension (HTN) has been linked to an elevated risk of prostate cancer (PC) development and poorer prognosis in localized cases, and is a common side effect of hormonal PC treatments. However, its relationship with the prognosis of metastatic PC is still unclear. We assessed the prognostic role of treatment-related HTN in patients with de novo metastatic hormone-sensitive PC (mHSPC) undergoing androgen deprivation therapy (ADT) alone or in combination with docetaxel or androgen receptor pathway inhibitors (ARPIs). Methods: Our retrospective analysis included 100 patients with de novo mHSPC treated with ADT, ADT + docetaxel, or ADT + ARPI between 2014 and 2021. Data on clinical variables, antihypertensive drugs, and blood pressure were collected from treatment initiation to 7 mo from ADT start. HTN development within 7 mo from hormonal treatment initiation was graded according to the Common Toxicity Criteria for Adverse Events version 5.0, and Cox analyses were performed for time to castration resistance (TTCR) and overall survival (OS). Key findings and limitations: In the overall population, grade (G) 2–3 HTN development within 7 mo from hormonal treatment initiation was associated with improved TTCR and OS at both univariate (TTCR: 19.8 vs 7.9 mo, hazard ratio [HR]: 0.35, 95% confidence interval [CI]: 0.20–0.63, p < 0.001; OS: 42 vs 18.4 mo, HR: 0.48, 95% CI: 0.26–0.87, p = 0.017) and multivariate (TTCR: HR: 0.41, 95% CI: 0.18–0.91, p = 0.029; OS: HR: 0.42, 95% CI: 0.18–0.97, p = 0.042) analyses. A subgroup analysis of the ADT + ARPI–treated population revealed 7-mo treatment-related G2–3 HTN to be an independent positive prognostic factor in terms of both TTCR and OS multivariate survival analyses (HR: 0.30, 95% CI: 0.09–0.95, p = 0.040, and HR: 0.12, 95% CI: 0.02–0.57, p = 0.008, respectively). Conclusions and clinical implications: The early development or worsening of HTN under hormonal treatment may be associated with longer TTCR and OS in de novo mHSPC patients. Larger studies are needed to validate these findings and explore the potential underlying mechanisms. Patient summary: In this report, we examined the outcomes of patients with metastatic hormone-sensitive prostate cancer and their correlation with hypertension toxicities. We found that patients who developed clinically significant blood pressure toxicity early in oncological treatment experienced longer survival.